Two new species of the genus Allosuctobelba (Acari, Oribatida, Suctobelbidae) from China - Zheng, Li-Hao; Duan, Hong-Bin; Chen, Jun (Zootaxa, 2024)
Two new species of the genus Allosuctobelba, A. (Allosuctobelba) polita sp. nov. and A. (A.) subiasi sp. nov., are proposed and described based on adult material collected from central China.